Evaluation of an Urban Drainage System in a Big City - Wisnu Prayogo; Sarra Rahmadani; Harry Wibowo; Laili Fitria; I Wayan Koko Suryawan; Nahesson H. Panjaitan; Putri Lynna A. Luthan; Novi Fitria (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Population growth has led to increased runoff and wastewater flowing into drainage channels. This study, therefore, aims to evaluate the drainage capacity of selected channels in Medan City and whether they can still serve the community in the next 10, 20 and 30 years. The observed channel starts from Taduan Street No. 1 to Taduan Street No. 153, with a length of 1,000 m. This evaluation considers population growth, the volume of domestic wastewater, the volume of runoff, the generation of sediment in channels, and evapotranspiration as part of the water cycle. Monthly maximum rainfall data from 2012-2021 from the BMKG Sampali Medan and population data along Taduan are used in the review in this article. Based on the investigation, it is known that the volume of drainage on Taduan Street is no longer able to serve the community even for 2032. It is necessary to review and redesign the dimensions to ensure that wastewater from household activities and runoff does not have a negative impact, especially during the rainy season. With as many as 48 injection wells and the Watershed expansion, it is expected to reduce inundation. Keywords:   Drainage channel, Domestic wastewater, Evaluation,  Medan, Rainwater